Pengaruh Penerapan Customer Relationship Management PT. Telkomsel terhadap Pelanggan KartuHALO di Kota Malang - Setyorini, Wahyu; Hadiwidjoyo, Djumillah (Jurnal Ilmiah Mahasiswa FEB, 2012)
Today, a lot of changes caused by the era of globalization. A rapid change and dynamic on all sides as in the field of technology, culture, economy, social, and others create a  tight pattern competition.  In technology, mobile phones or commonly called a cell phone while this is no longer goods expensive which can only be owned by certain society. An high interested public to a cell phone can be an opportunity for the provider telecommunication operator service providers to compete. In the condition of the competition marketing strategies that which concerns 4 P not easily used to clinch a share of the market because of competitors will also do the same thing so that the strategy tending to able to eat the high fees. Hence the need of innovation strategy practiced  by the business doers provider to be able to stand before competition PT. Telkomsel can get a great benefit when its customers are large amounts of these loyal on its products, but the threat also wide open if Telkomsel cannot keep the credibility of its service to customers and company. Hence, customer relationship management strategy implemented by  PT. Telkomsel to maintain credibility products and services to customers. To nurture and facilitate relations between Telkomsel and customers then company build a customer service offices Telkomsel named GraPARI that is short for of graha pari sraya. Besides as service offices, focusing to serve clients grapari also provides the sale of their products.Keywords : Customer Relationship Management, Identify, Differentiate, Interact, Customize, and Loyality